Efectos de fertilizante de liberación lenta, sobre el desarrollo y producción del cultivo de arroz (Oryza sativa L.), en la zona de Babahoyo - Polanco Mosquera, Jefferson Ricardo (2019)
This research work was carried out on the grounds of the experimental farm El Palmar of the Technical University of Babahoyo - CEDEGE Project, Los Ríos province, which is located at km 12 of the Babahoyo - Montalvo way, presenting a temperature of 25,6 ° C and a relative humidity of 82 %, with an annual rainfall of 2329.8 mm. As a planting material rice the SFL-11 variety was used. The treatments were formed Blaukorn ® in doses of 400 kg / ha, Blaukorn ® in doses of 300 kg / ha, Blaukorn ® in doses of 200 kg / ha, Blaukorn ® + FM in doses of 25 % + 75%, Blaukorn ® + FM in doses of 50 % + 50 %, Blaukorn ® + FM in doses of 75 % + 25 %, N-P-K-S mineral fertilization in doses of 550 kg/ha, Urea Witness in doses of 200 kg/ha, Farmer Witness (N-K-S) in doses of 300 kg/ha. The design that was used was completely randomized blocks, with nine treatments and three repetitions, for the calculation of analysis of variance the 95 % Tukey test was used. For the establishment of the trial, all relevant work was carried out, such as land preparation, planting, weed control, phytosanitary control, fertilization and harvest. For the results obtained, it was determined that the Blaukorn® slow-release fertilizer did not obtain the best results, contrary to the application of N-P-K-S mineral fertilization in doses of 550 kg/ha, obtaining the best results in the study variables such as the highest crop yield with 6296.40 kg/ha and net profit of $ 658.83.